SP0030 Reasons for delay in help seeking at the onset of symptoms. (12th June 2018) - Stack, R.J.
Abstract : Early intervention following the onset of chronic illnesses such as rheumatoid arthritis, lupus and Sjogren's syndrome can improve disease prognosis, reduce illness related disability and improve patient quality of life. Therefore, it is vital that the time between symptom onset and treatment is short, however, many patients experience long delays. The period of time between an individual's first detection of a bodily change and the first consultation with a healthcare professional is known as patient delay, while the time between first consultation and been referred to a rheumatologist for treatment is known as healthcare professional delay. Patient delay can be attributed to a range of barrier to consultation, these include contextual barriers (e.g. geographical location, financial barriers and availability of health services), individual barriers (e.g. demographic characteristics and health literacy) the nature of symptom onset (e.g. intermittent symptoms or the experience of a symptoms commonly associated with many conditions such as fatigue) and psychological barriers (e.g. perceptions of illness, the normalising symptoms interpretation of symptoms and fear and worries about wasting the doctor's time). Many interventions to reduce patient delay focus on educating the public about the typical symptoms associated with a specific illnesses in the hope that greater awareness will lead to better recognition of early symptoms. These interventions are based on the premise that the general public may hold misrepresentative stereotypes of what it is like to experience an illness or may even have no stereotypical belief (also known as a prototypical belief) to compare their current symptoms to. There is very little evidence about the evolution of early symptoms over time and how patients appraise these early symptoms and then decide to seek help. Furthermore, the non-specific nature of early symptoms for many rheumatological conditions can also be a significant barrier to patients recognising that symptoms are indicative of a chronic illness. For example, patients may attribute symptoms to stress, ageing or a temporary condition and actively choose not to seek help. Therefore, we must explore patients beliefs about symptom experience and not just focus on their beliefs about specific illnesses. Understanding early symptom presentation and the way that early symptoms are interpreted by patient is important for the development of robust help seeking interventions. However, interventions to promote prompt help-seeking based on symptom presentation must also take in to account for contextual, individual and psychological barriers which may interact with individual perceptions of early symptoms. Understanding the factors which lead to patient delays and healthcare professional delays across rheumatological conditions can ensure that interventions to reduce delay are developed using a robust evidence base. Evidence based interventions such be multifaceted and may include the development of public health information (e.g posters, tv campaigns etc), the development of robust online information and challenging mis-information online, addressing health inequalities which may lead to delay (e.g. increasing the accessibility of health services and promoting health literacy in hard-to-reach communities) and developing educational information for healthcare professionals. Disclosure of Interest: None declared